The Influence of the Hispanic-American avant-garde on young Spanish poetry - Snoey Abadías, Christian (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
The purpose of this article is to reflect on the influence of avant-garde Hispanic-American literature on young Spanish poetry, specially in the work of David Leo García and Berta García Faet. I will specially focus on the impact of writers such as César Vallejo and Oliverio Girondo, since there is yet an study in depth to be conducted regarding on the influence of Hispanic-American literature on young Spanish poetry. This study delve on two aspects: on the one hand, how the influence of the Hispanic-American avant-garde influence has tinged the reflection on the use of the language on these writers’ works and, on the other hand, the way in which Hispanic-American avant-garde has shaped the forming of the poetic subject within the text and in which manner this has transformed its formal entity. I will study this matter throughout the dissertation on the works Nueve meses sin lenguaje, by David Leo García, along with Los salmos fosforitos, by Berta García Faet.